The Effect of Reward and Punishment Policy on the Productivity of BPJS Health Employees Kotabumi Branch Office - Fadhilah Faiqoh; Sidrotun Naim; Deden Rahmanudin; Feb Amni Hayati; Sabil Mokodenseho (Tadbir : Jurnal Studi Manajemen Pendidikan, 2022)
The discipline of employees regarding working hours at the office of BPJS Health Kotabumi Branch is still relatively low. This low discipline of employees towards working hours can cause a lack of employee productivity. Problems concerning discipline in a company or government agency must be solved by making policies to overcome them. This study aimed to analyze the effect of implementing reward and punishment policies as a solution to increase employee productivity. The type of this study was field research with the quantitative method to analyze the obtained data. Samples in this study were 30 employees of BPJS Health for Kotabumi Branch, selected using the total sampling technique. Meanwhile, to analyze the obtained data, the researcher used multiple linear regression analysis. The results of the calculations using the Multiple Linear Regression analysis at a significance level of a=0,05, showed as follows. First, the p-value for H_0A was 0.02 (< 0.05), meaning that H_0A was rejected, concluding that the reward policy had an effect on increasing employee performance productivity. Second, the p-value for H_0B was 0.00 (< 0.05), meaning that H_0B was also rejected, concluding that the punishment policy had an effect on increasing employee performance productivity. Third, the p-value for H_0C was 0.00 (< 0.05), meaning that H_0C was rejected, concluding that the reward and punishment policy had an effect on increasing employee performance productivity. These findings contributed to increasing the productivity of employee performance. In addition, they can be used by policymakers in a company for increasing the productivity of employee performance.